Metode Pembelajaran Demonstrasi dalam Meningkatkan Kemampuan Membaca Anak Usia Dini TK Kartika Jombang - Afisya Paradisa; Naili Sa’dah; Wardah Suweleh (J-SES : Journal of Science, Education and Studies, 2023)
The aim of this research is to determine the application of the demonstration learning method in improving the reading skills of young children at Kindergarten Kartika Jombang. Quantitative research method with descriptive and inferential approaches. The population in this study is Kartika Kindergarten. Sampling was carried out using the purposive sampling method. Data collection techniques were carried out by distributing pretests and posttests. The research method used to test the hypothesis is with the help of SPSS software. 16.00 for windows. It is known that the significance value of Sig. (2-tailed) is 0.000 < 0.05, then Ho is rejected and Ha is accepted. It is known that t calculated has a negative value of -36,877. This t-count has a negative value because the average pretest learning score is lower than the average posttest learning result so that the t-count becomes t-count -36.877 > t-table 2.110, which means that the basis for decision making is that Ho is rejected and Ha accepted, so it can be concluded that there is a difference between the average pretest and posttest of the implementation of the demonstration method on the reading ability of early childhood children at Kindergarten Kartika Jombang.